AN ANALYSIS OF THE INTRINSIC ELEMENTS AND MORAL VALUES IN TETSUKO KUROYANAGI'S NOVEL "TOTTO CHAN: THE LITTLE GIRL AT THE WINDOW" - Ardayati, Ardayati; Rahayu, Asih (English Community Journal, 2017)
The objectives of this research were to find out the intrinsic elements and the moral values in Totto Chan: the Little Girl at the Window novel. This research employed descriptive qualitative as the method. The data were collected by using library research. Intrinsic elements involved theme, character and characterization, plot, setting and point of view. Moral values in this novel were honesty, willingness to take responsibilities, independence and humility. Research result showed that the education was applied well in Tomoe Gakuen. Tomoe Gakuen was the real form of a wanted dream school. Mr. Kobayashi asthe headmaster managed to create his dream school in Japan, even in the World War II period.